Exploring Student and Faculty Perspectives on Professionalism in Occupational Therapy Education. - Roberts, Mary Roduta; Barton, Jilaine; Janzen, Amy; Johnson, Carolina; Painchaud, Lauren (Open Journal of Occupational Therapy (OJOT))
The development of professionalism is critical for occupational therapy (OT) students to become competent occupational therapists. This paper reports on the first phase of a multi-phase project to develop and pilot a situational judgement test to support teaching, learning, and development of professionalism in an OT program. The purpose of this study was to explore faculty and students' perspectives on professionalism and OT. Twenty-two semi-structured interviews were completed with students (n = 18) and faculty (n = 4). The main insights shared included challenges in defining professionalism in OT, the importance of context, and differing perspectives on the effectiveness of teaching professionalism in the curriculum. A working definition is proposed to facilitate a shared understanding of professionalism and inform the development of professionalism scenarios.